The role of milk-derived exosomes in the treatment of diseases - Rashidi, Mehdi; Bijari, Salar; Khazaei, Amir Hossein; Shojaei-Ghahrizjani, Fereshteh; Rezakhani, Leila (Frontiers in Genetics, 2022)
Exosomes (EXOs) are natural nanoparticles of endosomes origin that are secreted by a variety of cells in the body. They are also present in the body's biological fluids, including milk. These nanoparticles play an important and complex role in cellular communication. Due to the presence of specific proteins, lipids, and RNAs, they act in physiological and pathological conditions in vivo. Other salient features of EXOs include their long half-life in the body, no tumorigenesis, low immune response, good biocompatibility, ability to target cells through their surface biomarkers, and capacity to carry macromolecules they introduced to the scientific community as important, efficient, and attractive nanoparticle. EXOs can be extracted from different sources and have the same characteristics as their parents. As a rich source of EXOs, milk has unique properties that, in addition to its role as a carrier, findings in favor of treating diseases such as digestive problems, skin ulcers, and cancer have been reported. Mammals milk isolation due to their availability, non-invasiveness, and cost-effectiveness of their preparation can be introduced as an excellent resource in studies related to EXOs. These features also make it possible to commercialize milk-derived exosomes (MDEs) in clinical trials. The focus of this study is to investigate the therapeutic applications of EXOs isolated from various milk sources.